A Theology of the Religions and/or a Comparative Theology? - Duffy, Stephen J. (Horizons, 1999)
An important but little-noticed debate is quietly going on between some theologians of the religions and some comparative theologians. The former, without negating the need for comparative theology, insist on the need for a theology of the religions; the latter call for a moratorium on construction of theologies of religion and a focus instead on comparative work. This essay sides with the theologians of religion and argues that contrary to the one-sided position of the comparativists and the premature judgments of some theologians of the religions, there is a need for both a theology of the religions and comparative analysis and synthesis because the two are the distinct but inseparable and integral a priori and a posteriori moments of a single theological project which aims at bringing Christianity into fruitful engagement with the non-Christian traditions. Because this engagement is essential to Christianity, the present debate is an important one even though it goes on in a field little tended, unfortunately, but many theologians.